Multiple Evaluation Options & Comparability: Equity Investments in Italy and Spain - Simona Catuogno; Alessandra Allini (Journal of Accounting and Management Information Systems (JAMIS), 2011)
The harmonization among the European financial statements based on International Accounting Standards/International Financial Reporting Standards (IAS/IFRS) became an urgent issue when the European Union issued the Regulation (EC) no 1606/2002 which required all listed companies to prepare consolidated accounts in accordance with International Accounting Standards beginning in 2005. The enforcement of the same set of accounting standards does not necessarily lead to comparability if we intend it as a harmonization of the accounting practices. As a matter of fact, European companies could still choose divergent accounting behaviors because IAS/IFRS offer multiple options for the evaluation of the same items, or because the accounting practices of those firms do not comply with the standards. The objective of this paper is to investigate if the level of comparability in consolidated financial reporting practices – as a result of de facto harmonization – has increased after the mandatory introduction of IAS/IFRS. To provide some evidence, the case studies of Italy and Spain have been elected since they are both Code law countries. First of all we test the level of de facto harmonization related to the accounting choices made by 129 Italian and 54 Spanish listed groups, from 2004 to 2009, that is pre and post IAS/IFRS application, in order to verify if the comparability between countries in policy choices, as measured by van der Tas C index, has changed after the application of IAS/IFRS, from the point of view of the users of the financial statements. Starting from the assumption that the de facto harmonization of the accounting practices increases the comparability among firms and among countries, the current study contributes to the literature by exploring the following main research question: Do harmonized accounting standards lead to comparable accounting practices, even when multiple evaluation options are provided? More precisely, comparability has been measured referring to the items of equity investments in subsidiaries, in associates, in joint ventures, and in other equity interests, since the participation item is an excellent setting for this kind of investigation. First results seem to reveal that we are still quite far from the expected and desired comparability. These findings could be helpful for the decisions of institutional regulatory bodies.
Keywords: M41; 650; IFRS; Comparability; Harmonization; Equity investments